Duststorm measurements for the prediction of attenuation on microwave signals in Sudan - Elabdin, Zain; Islam, Md. Rafiqul; Khalifa, Othman Omran; Ismail, Ahmad Faris (2008)
The Lack of observation on microwave signal propagation during duststorm in Sahara region and Middle East stimulated the present work. Investigation on the characteristics of duststorm and its effect on microwave signal propagation have been presented. A physical models of duststorm from measured data proposed. This paper has presented a study on microwave propagation carried out in Sudan using existing microwave links monitoring by Marconi microwave monitoring system with the calibration of the meteorological data recorded in Sudan. The paper has also investigated and compared the measured attenuation with the value calculated by the mathematical prediction models.